DETERMINATION OF SOME HEAVY METALS RESIDUES IN RAW MILK OF COWS , SHEEP AND GOATS IN Al-QADISIYA GOVERNORATE - & Ali, Taher (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out in Al-Qadisiya Governorate during the period from December , 2012 to March , 2013. Involving five regions with different geographical locations (Diwania city center , Saniya District , Shafeia District, Daghara District and Al-Hamza District ) to determine the residues of nickel , arsenic and mercury in raw milk of cows , sheep and goats . A total of 150 raw milk samples were collected from 150 animals belong to the three species, involved 50 samples for cows, 50 samples for sheep and 50 samples for goats (10 samples / region) selected randomly. Atomic absorption spectrophotometry  was used to determine the concentration of nickel (NI) , arsenic (AS) and mercury (Hg) . The results showed that a significant differences (p